O07.1 Sexual Relationship Importance and Condom Use Among Men Attending STD Clinics in Two Southern Cities in the United States. (13th July 2013) - Kissinger, P; White, S; Schmidt, N; Taylor, S N; Mena, L; Lillis, R; Some, S; Defayette, K; Adamski, A; Rosenthal, S L
Abstract : Background: Relationship type and perception of importance of the relationship may be predictors of condom use. Methods: Men who presented at STD clinics in New Orleans, LA and Jackson, MS with NGU, tested positive for Chlamydia trachomatis (Ct), or were contacts of women with Ct underwent computer-assisted/self-administered interviews and were asked to report information on up to 4 sexual partners in the last two months. Importance of relationship was determined using 4 variables: having history together, shared feelings, commitment to each other, and physical passion. Results: 1065 men reported information on 1924 partnerships; 98.9% of which were with women, 47% were considered main, but only 30% of the men lived with and 6% were married to main partners. Relationships were described as: girlfriend/boyfriend (32%), mother-of-child (6.8%), friend-with-benefit (26.4%), sex with but not friend (6.2%), ex-girlfriend/boyfriend (9.1%), someone I want to have relationship with (5.8%), one night stand (12.3%), paid for sex (1.4%). Most (82.1%) had sex in a home, while 11.3% in hotel, and 6.6% in public place/other. Importance of relationship variables by relationship (most important to least 1–8) were: girlfriend/boyfriend (1.1) and mother-of-child (1.7), and someone I might want to have a relationship (2.6), ex-girlfriend/boyfriend (3.7), friend-with-benefit (5.3), sex but not friend (6.8), paid for sex (7.1) and one night stand (7.2). The less important the relationship was, the more likely they were to be using a condom O.R. 1.13 (95% C.I. 1.08–1.18). Condom use at last sex act was least likely with the mother of child (34.5%) and most likely with paid to have sex (91.7%). Condom use was between 51% - 78% for the other categories. Conclusion: In general, condoms were used more frequently with partners whose relationships were perceived as less important, but this was not universal.